ACTIVITIES OF THE ARCHITECTURAL DEPARTMENT ON THE CONSTRUCTION OF THE HOUSE OF THE ODESSA BRANCH OF THE IMPERIAL TECHNICAL SOCIETY (Південний архів (історичні науки), 2024)
The purpose of the study is to analyze the activities of Odessa architects – members of the Odessa branch of Imperial Russian Technical Society (OBIRTS) for the design and construction of the building, to study the fate and role of this structure in the culture of a large city. The methodology is based on the principles of historicism, systematicity, and author’s objectivity. General scientific (analysis and synthesis) and general historical (historical-genetic, historicalsystemic) research methods were used. Results. It was established that the idea of construction and design of the building of the Odessa branch of IRTS belonged to the members of the architectural department of OBIRTS. This building is known as the “Masonic House” in Odessa. The construction process from design to interior creation lasted 8 years. The OBIRTS building was an object of cultural heritage of Odessa, located at 1a Knyazheskaya Street. Conclusions. The postreform period of the second half of the 19th century contributed to the development of the creative initiative of engineers, architects, builders, industrialists and entrepreneurs of the South of Ukraine. The creation of the Odessa branch of IRTT, the activities of all its 9 departments contributed to the scientific and professional-technical modernization of the South of Ukraine. The creative initiative of the members of OBIRTS and the bold decisions of its architectural and construction departments contributed to the formation of the architectural appearance of Odessa. The OBIRTS building they created decorated Odessa. The city professionals built and decorated this building. The architectural heritage of Odessa has monuments and complexes that are valuable for history, culture and architecture. They convey the spirit of the era, demonstrate the initiative and professionalism of creative people. The protection and interpretation of architectural heritage are important tasks because they contribute to the preservation and transfer of knowledge and values to future generations.
Keywords: history of Ukraine, post-reform period, technical society, architectural department, Odesa branch of the Imperial Russian Technical Society.